Effect of Health Literacy Program on Improving Elderly Women’s Self-Care Practice Regarding Atrophic Vaginitis - Aya Hamada Mohammed Mohammed (The International Journal of Multiphysics, 2024)
Background: Aging is associated with many different health-related challenges for women such as menopause and its associated problems. Atrophic vaginitis affects 10 to 40% of postmenopausal women worldwide. Self-care (SC) is a factor with potential effects on menopause and its consequences. Self-care education based on health literacy has the potential to improve menopausal women’s self-care. The aim of the study was to evaluate the effect of Effect of health literacy program on improving elderly women’s self-care practice regarding atrophic vaginitis. Subjects and Methods: Research design: A quasi-experimental design was adopted to carry out this study. Setting: The study was conducted at Geriatric Social club at Zagazig city. Subjects: Purposive sample of 70 elderly women who fulfilled the study inclusion criteria. Tools for data collection: Tool I: A structured interview questionnaire was used for data collection. It was composed of three parts. (Part I) elderly women demographic characteristics, (Part II) medical and obstetric history and (Part III) Risk factors of atrophic vaginitis. Tool II: Self-care practice of elderly women regarding atrophic vaginitis. Results: Out of the 70 elderly women, only 38.6% of the studied elderly women had adequate level of self-care regarding atrophic vaginitis pre the program which improved to 74.3% post program. Additionally, there was a highly statistically significant positive correlations between the studied elderly women’ knowledge, self- care practice pre and post program at (p < 0.01), and there was a highly statistically significant difference between pre & posttest program as regarding health literacy self- care practice about atrophic vaginitis for elderly women. Conclusion: The health literacy program produced substantial, clinically meaningful improvements in self-care among elderly women with atrophic vaginitis, translating into better hygiene practices. Recommendations: Integrating culturally tailored education into geriatric and primary care pathways which, encourage healthy and positive self-care about atrophic vaginitis in women in early age rather than teaching them when grown up.